2021
DOI: 10.3390/rs13112140
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Image Quality and Light Consistency on the Performance of Convolutional Neural Networks for Weed Mapping

Abstract: Recent computer vision techniques based on convolutional neural networks (CNNs) are considered state-of-the-art tools in weed mapping. However, their performance has been shown to be sensitive to image quality degradation. Variation in lighting conditions adds another level of complexity to weed mapping. We focus on determining the influence of image quality and light consistency on the performance of CNNs in weed mapping by simulating the image formation pipeline. Faster Region-based CNN (R-CNN) and Mask R-CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…It should be noted that Cot2 differed from Cot1 in three aspects: (1) Cot2 had a relatively higher density of weeds and the median size of MG and Grass differed from that of Cot1, (2) some of the cotton plants in Cot2 had slightly different visual appearance due to herbicide drift, and (3) the illumination conditions for Cot2 was slightly darker than that of Cot1. Hu et al (2021) suggested that illumination conditions can affect weed detection accuracy. With respect to herbicide drift impact, Suarez et al (2017) found in cotton that drift can lead to a significant change in the spectral behavior of the crop.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that Cot2 differed from Cot1 in three aspects: (1) Cot2 had a relatively higher density of weeds and the median size of MG and Grass differed from that of Cot1, (2) some of the cotton plants in Cot2 had slightly different visual appearance due to herbicide drift, and (3) the illumination conditions for Cot2 was slightly darker than that of Cot1. Hu et al (2021) suggested that illumination conditions can affect weed detection accuracy. With respect to herbicide drift impact, Suarez et al (2017) found in cotton that drift can lead to a significant change in the spectral behavior of the crop.…”
Section: Resultsmentioning
confidence: 99%
“…Several image-based weed detection techniques have been proposed and implemented. Based on developments made so far, these techniques can be broadly categorized into two main groups: (1) traditional segmentation and machine learning-based techniques ( Wu et al, 2011 ; Ahmed et al, 2012 ; Rumpf et al, 2012 ; García-Santillán and Pajares, 2018 ; Sabzi et al, 2018 ; Sapkota et al, 2020 ) and (2) advanced computer vision using convolution neural networks (CNNs; Adhikari et al, 2019 ; Ma et al, 2019 ; Sharpe et al, 2020 ; Hu et al, 2021 ; Xie et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e camera overexposure addition operation in this study is similar to other pieces of literature [56]. e number of interval frames at which overexposure interference is added ranges from 30 to 10 and is decreased by a step size of 5. e results are shown in Table 9.…”
Section: About Differentmentioning
confidence: 95%
“…As one of the objectives of this study is to investigate the feasibility of automatic garment sizing with household photographs that can be uploaded to different platforms (e.g., second-hand clothing platforms) photos taken under different conditions and with different mannequins or hanging on a hanger have been included. There are solutions for overcoming the effects of lighting and occlusion, but they are usually developed for specific groups of objects [12,23] or noises [24].…”
Section: Methodsmentioning
confidence: 99%